Diversity and Distribution of Bunomys (Rodentia: Muridae) Along an Elevational Gradient in Gandang Dewata National Park - Yusuf Sama; Muhammad Rizaldi Trias Jaya Putra Nurdin; Alexander Kurniawan Sariyanto Putera; Nurmiati; Maipa Dia Pati (Indonesian Journal of Ecology and Conservation, 2025)
This study aimed to determine the distribution and diversity of the genus Bunomys in Gandang Dewata National Park. Fieldwork was conducted in July 2025 using live traps placed across several habitat types and different elevation ranges. Data collection was carried out by installing traps along transect lines at locations suspected to be rat movement pathways. The collected data were analyzed descriptively to identify species and describe their distribution patterns. The results revealed the presence of three species within the genus Bunomys: Bunomys penitus, Bunomys andrewsi, and Bunomys torajae. Each species exhibited different habitat preferences. A total of 16 individuals of B. penitus were found at mid-elevations with primary forest vegetation at elevations ranging from 1,588 to 1,912 m above sea level. Nineteen individuals of B. andrewsi were recorded in secondary forest habitats at elevations between 1,509 and 2,154 m above sea level. Meanwhile, B. torajae was represented by eight individuals found in high mountain areas at elevations of 2,561–2,596 m above sea level. These findings provide important information on the distribution of the genus Bunomys in Sulawesi and highlight the role of Gandang Dewata National Park as an important habitat for endemic wildlife. This study also contributes to enriching the limited biodiversity data on small mammals in the mountainous regions of Sulawesi. Further studies focusing on ecological aspects, behavior, and genetic analysis are recommended to deepen the understanding of population dynamics and phylogenetic relationships within the genus Bunomys